Systematic literature review of treatment patterns for venous thromboembolism patients during transitions from inpatient to post-discharge settings - Trocio J; Rosen VM; Gupta A; Dina O; Vo L; Hlavacek P; Rosenblatt L (Dove Medical Press, 2018)
Jeffrey Trocio,1 Virginia M Rosen,2 Anu Gupta,3 Oluwaseyi Dina,1 Lien Vo,4 Patrick Hlavacek,1 Lisa Rosenblatt5 1US Health Economics and Outcomes Research Pfizer Inc., New York, NY, USA; 2Health Economics and Outcomes Research, Optum Inc., Eden Prairie, MN, USA; 3US Medical Affairs, Pfizer Inc., New York, NY, USA; 4US Health Economics and Outcomes Research, Bristol-Myers Squibb, Lawrenceville, NJ, USA; 5US Medical Affairs, Bristol-Myers Squibb, Lawrenceville, NJ, USA Introduction: Direct oral anticoagulants (DOACs) have emerged as viable alternatives to traditional treatments such as vitamin K antagonists (VKAs) for venous thromboembolism (VTE). The objective of this review was to summarize evidence on the use of DOACs and VKAs to treat VTE in the US for patients transitioning from inpatient to post-discharge settings. Materials and methods: A systematic review of the VTE literature identified studies published in English (January 1, 2011–December 31, 2016) that reported inpatient and post-discharge treatments and discharge location. Two reviewers screened abstracts, abstracted information from included studies, and assessed the quality of the study methodology and reporting. Results: Forty-nine studies were included (24 clinical and 25 economic). A limited number of studies (eight clinical and three economic) examined VTE treatment patterns during transitions of care from inpatient to post-discharge settings, irrespective of anticoagulant (eg, DOAC, warfarin, heparin), and < 25% of all studies reported a post-discharge location. Three clinical studies that reported inpatient and outpatient treatment found better patient outcomes with DOAC vs warfarin. Fourteen economic studies reported that DOACs were associated with shorter hospital length of stay (LOS) and lower direct costs vs warfarin. No studies reported indirect costs. Discussion: Although DOACs are associated with shorter LOS, lower costs, and better patient outcomes vs VKAs, it appears in one study that only a small percentage of patients with stable VTE who are discharged to home may be receiving DOACs. Conclusion: These findings identified the potential areas of opportunity to improve the management of VTE through coordination of care from the inpatient to the outpatient settings. Keywords: deep vein thrombosis, pulmonary embolism, anticoagulant, transition of care